JUDICIAL ACTIVISM ON THE MERIT OF PUBLIC ADMINISTRATION - Thomas Gubert, William (Revista Gênero e Interdisciplinaridade, 2023)
The present work in article format analyzes the concepts, applications and repercussions extracted between the terms Judicial Activism, Administrative Merit and Administrative Discretion. The objective is to examine, explain well, signify, separate and, where possible, correlate the three institutes above. To this end, a brief literature review was carried out on the Constitutional Principles Applicable to the study and research themes: Legality, Judicial Control of Public Administration and Jurisdictional Inalienability; as well as - by the same bibliographical methodology - of the trio indicated in the first paragraph. The diagnosed data revealed that they are distinct legal spaces and contents, however relatable to each other; above all for a skillful technical and hermeneutic dialogue in the light of the Federal Constitution and the other regulations of the Brazilian Legal Order.